En god (om)vej til mere rekreativ fysisk aktivitet i hverdagen - Troelsen, Jens; Pawlowski, Charlotte Skau (Forum for Idræt, 2013)
A circuitous way to more recreational physical activity Background: The scientific evidence available supports the overall conclusion that sedentary behavior is a threat to public health. The population in the western societies is far from meeting the global guidelines for physical activity (PA). However, supportive built environment for PA has proven to be way to prevent the incidence of physical inactivity. The Danish intervention study “En God Omvej” was initiated to investigate how the construction of different types of activating facilities influences PA behavior in a local arena. The knowledge gained will help understand how to optimize development of physical interventions to promote recreational PA. Levels of recreational PA are primarily associated with motivation, timing, and physical, mental and social resources. The built environment has a vital part to play in encouraging and supporting healthy active living. The “En God Omvej” study has shown the importance of accessible locations, simple functionality and maintenance. These aspects must be prioritized in planning, especially with the ambition to attract and sustain a regular, everyday use. For more in-depth knowledge studies identifying facilitators and barriers related to recreational PA are important in the effort to develop activating facilities in interaction with the specific location and the local residents.